Physical Mechanisms and Theoretical Computation of Efficiency of Submicron Particles Agglomeration by Nonlinear Acoustic Influence - Vladimir N. Khmelev; Andrey V. Shalunov; Roman N. Golykh (Aerosol and Air Quality Research)
Abstract This study models the agglomeration of submicron particles when they are exposed to different types of ultrasonic waves, viz., sinusoidal waves and shock waves (pulses). The nonlinear effects of the shock waves (the transfer of heat, drop in pressure, change in the particles’ collisional cross-section due to Brownian motion, and difference in particle concentration), which influence the particle coagulation rate, are simulated for the first time and evaluated. The results reveal the optimum duration for compression and depression shock-wave pulses. Furthermore, given the same total amount of ultrasonic energy, the submicron particles coagulate 20 times more quickly with shock waves than sinusoidal waves.